Impact of climatic and water quality parameters on Tilapia (Oreochromis niloticus) broodfish growth: Integrating ARIMA and ARIMAX for precise modeling and forecasting - Mohammad Abu Baker Siddique; Balaram Mahalder; Mohammad Mahfujul Haque; A. K. Shakur Ahammad (PLoS ONE, 2025)
This study aims to assess the impact of climatic factors and water quality parameters on the growth of tilapia broodfish and develop time series growth models using ARIMA and ARIMAX. Three years longitudinal data on tilapia growth, including length and weight were collected monthly from February 2021 to January 2024. Climatic data were obtained from the Bangladesh Meteorological Department, while water quality parameters in the broodfish pond were measured daily on-site. Key variables such as air temperature, humidity, rainfall, solar intensity, water temperature, dissolved oxygen (DO), pH, and ammonia, showed fluctuation in the ponds. The highest growth rate (5.93%) occurred in April, and the lowest (0.023%) in December. Overall, tilapia growth in weight followed an exponential trend, while the percent growth rate exhibited a seasonal pattern. Pearson correlation analysis indicated a significant association between growth increments and water quality parameters. The ARIMA (3,0,3) model predicted a consistent upward trend in tilapia weight from February 2024 to January 2027. If the pattern continues, the estimated weight of tilapia will reach 803.58 g by the end of January 2027, a 17.05% increase from January 2024, indicating a positive outlook for broodfish health and production. However, the ARIMAX (1,1,1) model for percent weight gain revealed seasonal fluctuations that were strongly influenced by water temperature and solar intensity. Over the three-year period, forecasts indicated a downward trend in percent weight gain during the first year, followed by an upward trend in the second and third years. This indicates the influence of seasonal changes on percent weight gain. The simulation behaviors were consistent with the forecasted trend. These findings have important implications for planning and managing tilapia broodfish production, highlighting the need to consider environmental factors in future aquaculture management.